Perbandingan Inferensi Kausal Versi Donald Campbell dengan Donald Rubin - T Dicky Hastjarjo (Buletin Psikologi, 2018)
In a psychological experiment, the manipulation of the independent variable is deliberatelyintroduced to observe its effects on the dependent variable. The cause-effect relationshipthen is inferred. This article explained briefly two models of causal inferences. One modeldeveloped by Donald Campbell is more focused on design elements in ruling out threats tovalidity. On the other hand, Rubin’s model of causal inference emphasized in mathematicalprecision of the causal effects. The comparison of the two different but complementarymodels involves both randomized experiment and observational study.